Biologia floral e reprodutiva de guabijuzeiro, sete-capoteiro e ubajaizeiro - Guollo, Karina (2019)
Studies with species Myrtaceae family are mostly distributed in floristic surveys, reproductive studies involving large plant communities or those related its taxonomy. The aim was to elucidate aspects of the floral and reproductive biology of guabiju tree, sete-capote tree and ubajai tree. Studies were carried out on floral morphology and morphometry, a moment of the anthesis and androecium maturation, identification of nectaries and attractive structures for floral visitors, characterization of pollinators and floral visitors, stigma receptivity, pollen storage and germination in vitro, and characterization of the reproductive system. Guabiju tree has hermaphrodite flowers, and the floral opening occurs mainly during the night, but also in the morning. Anthers are the main attractive structure to pollinating insects, releasing fetid odor, attracting mainly flies and wasps characterized as occasional pollinators, and moths characterized as effective pollinators. For the germination of pollen it was recommend using it without desiccation, collected in post-anthesis, and for the culture medium the use of 11% of sucrose and 7% of boric acid. Pollen had recalcitrant behavior, so even when stored in refrigerator, freezer, liquid nitrogen and natural environment it lost viability in less than 30 days. It presents high reproductive efficacy, and it can be considered self-compatible, however, fertilization also occurs through cross-pollination. Sete-capote tree has hermaphrodite flowers, and the floral opening occurs mainly during the nocturnal period, however, it also occurs in the morning. Pollen grains are the main resource offered to pollinators. The flowers have a mild sweet odor attracting mainly native bees and Apis mellifera, which was characterized as effective pollinators. For the germination it recommended the use of pollen from flowers in post-anthesis, dehydrated for 24 hours in a silica chamber. The culture medium should contain 12% sucrose, 10% boric acid and 20% calcium nitrate to obtain high germinative percentages. Still, pollen presents orthodox behavior and when stored in liquid nitrogen, remains viable for 30 days. The species presents high reproductive efficiency, and can be considered self-compatible; however, fertilization also occurs through cross-pollination. Ubajai tree has hermaphrodite flowers, the floral opening is diurnal. The anthers are the main attractive structure to the pollinating insects, and it releases odor in fruity notes, slightly sweet. The main floral visitors of the species belong to the families Apidae, and Chrysomelidae, being Apis mellifera the effective pollinating species of flowers of the ubajai tree. The addition of 40% sucrose to the culture medium using fresh pollen grains from pre-anthesis flowers is sufficient for germination to reach 90%. Pollen from ubajai flower presents recalcitrant behavior, so even when stored in the refrigerator, freezer, liquid nitrogen and natural environment lose viability in less than 30 days. The ubajai tree can be considered self-compatible, however, the fertilization of the flowers also occurs by cross-pollination, and asexual reproduction does not occur. This information will be useful and essential for the development of future work, such as improvement projects and dissemination of knowledge for exploitation and training of commercial orchards.